Microstructure of the linguliformean brachiopod Linnarssonia from the Lower Cambrian of Sichuan, China - Feng, WM (冯伟民); Kobayashi, I (Lethaia, 2004)
Acrotretoids, one of the oldest brachiopod groups, are abundant in the Lower Cambrian Jiulaodong Formation. The shell of Linnarssonia sp. is composed of two layers: a primary layer and a columnar secondary layer. The primary layer is mostly exfoliated, resulting in exposure of the openings to the central canal of the columns. Filae are seen on the surface of the columnar layer, indicating that the columnar secondary layer has influenced changes in ornament on the shell surface. The larval shell has only very weak ripples; the post-larval shell has obvious concentric ribs. Small pits of variable shape cover almost the entire shell surface. The secondary layer is composed of several columnar laminations, each of which comprises both the upper and lower laminae and the cylindrical columns between them. On the inner side of shell the thin columnar laminations increase. The new microstructural data show that two shell layers are developed in Early Cambrian acrotretoid brachiopods; the columnar lamination may be a primitive feature of the microstructural development of the Brachiopoda and may help establish the affinity between different stem-group brachiopods.